2013
DOI: 10.1371/journal.pone.0073427
|View full text |Cite
|
Sign up to set email alerts
|

A Floating Bridge Disrupts Seaward Migration and Increases Mortality of Steelhead Smolts in Hood Canal, Washington State

Abstract: BackgroundHabitat modifications resulting from human transportation and power-generation infrastructure (e.g., roads, dams, bridges) can impede movement and alter natural migration patterns of aquatic animal populations, which may negatively affect survival and population viability. Full or partial barriers are especially problematic for migratory species whose life histories hinge on habitat connectivity.Methodology/Principal FindingsThe Hood Canal Bridge, a floating structure spanning the northern outlet of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…A substantial portion of the HCB to ADM mortality may be associated with the Hood Canal Bridge itself. Detailed behavioral analysis suggests that the Hood Canal Bridge causes migration delays and abnormal movement patterns that may increase predation on steelhead smolts in the vicinity (Moore et al 2013). Although steelhead smolt populations typically experience their highest mortality rates during their initial marine migration segment, habitat-specific conditions can contribute substantially to variation in mortality rates among regions.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial portion of the HCB to ADM mortality may be associated with the Hood Canal Bridge itself. Detailed behavioral analysis suggests that the Hood Canal Bridge causes migration delays and abnormal movement patterns that may increase predation on steelhead smolts in the vicinity (Moore et al 2013). Although steelhead smolt populations typically experience their highest mortality rates during their initial marine migration segment, habitat-specific conditions can contribute substantially to variation in mortality rates among regions.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting theories exist on whether near-or offshore marine environments exert the greatest impact on mortality of Salish Sea steelhead. Welch et al (2004) provided evidence, using stationary acoustic receivers, that survival was lower in the open-ocean marine environment, and Moore et al (2010Moore et al ( , 2013 provided evidence, also using stationary acoustic receivers, that survival was lower in the nearshore marine environment. More recently, Melnychuk et al (2013) suggested that the use of both stationary acoustic receivers and mobile tracking could improve the detectability of the actual locations in the marine environment at which mortality occurs in steelhead.…”
Section: Observed Sr (Mm)mentioning
confidence: 99%
“…Recent studies of steelhead in the Salish Sea have highlighted the importance of survival in marine environments, but locations and modes of mortality have not been conclusively determined. Steelhead smolts in the Salish Sea do not appear to spend time foraging and growing in local estuarine or brackish environments (Melnychuk et al 2007;Moore et al 2010), but environmental conditions in both nearshore marine waters (Moore et al 2010(Moore et al , 2013Melnychuk et al 2013;Romer et al 2013) and the high seas of the Pacific Ocean influence marine survival and production of many anadromous salmonid stocks in this region (Welch et al 2000;Welch et al 2004;Moss et al 2005;Melnychuk et al 2007;Welch et al 2011;Atcheson et al 2012). Using an 18-year data series, Atcheson et al (2012) found that the growth of steelhead in the high seas varied with oceanic conditions.…”
Section: Observed Sr (Mm)mentioning
confidence: 99%
“…Docks, piles, and bridges are discrete structures that influence interactions between predatory fish and their prey. The effects of these structures can be compounding: they can disrupt or delay movements of migratory species such as salmon while simultaneously aggregating predators (Moore et al 2013).…”
Section: Contact Point Typesmentioning
confidence: 99%
“…Specifically, ambush predators may benefit from the decreased light and shelter under docks, while roving predators do not. Some studies found that fishes aggregated near docks but not under them (Moore et al 2013). However, docks may also be attractive to predator and prey species alike because they increase habitat complexity and provide shelter.…”
Section: Docks and Piersmentioning
confidence: 99%